If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(3 + -2y) + -3(sm + -1) = 9 (3 * y + -2y * y) + -3(sm + -1) = 9 (3y + -2y2) + -3(sm + -1) = 9 Reorder the terms: 3y + -2y2 + -3(-1 + ms) = 9 3y + -2y2 + (-1 * -3 + ms * -3) = 9 3y + -2y2 + (3 + -3ms) = 9 Reorder the terms: 3 + -3ms + 3y + -2y2 = 9 Solving 3 + -3ms + 3y + -2y2 = 9 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3ms + 3y + -3 + -2y2 = 9 + -3 Reorder the terms: 3 + -3 + -3ms + 3y + -2y2 = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -3ms + 3y + -2y2 = 9 + -3 -3ms + 3y + -2y2 = 9 + -3 Combine like terms: 9 + -3 = 6 -3ms + 3y + -2y2 = 6 Add '-3y' to each side of the equation. -3ms + 3y + -3y + -2y2 = 6 + -3y Combine like terms: 3y + -3y = 0 -3ms + 0 + -2y2 = 6 + -3y -3ms + -2y2 = 6 + -3y Add '2y2' to each side of the equation. -3ms + -2y2 + 2y2 = 6 + -3y + 2y2 Combine like terms: -2y2 + 2y2 = 0 -3ms + 0 = 6 + -3y + 2y2 -3ms = 6 + -3y + 2y2 Divide each side by '-3s'. m = -2s-1 + s-1y + -0.6666666667s-1y2 Simplifying m = -2s-1 + s-1y + -0.6666666667s-1y2
| 20=-0.66x | | (x+y^2)*(8x+y^2)= | | 4(3a-1)-5(1-a)=8 | | (3s+6t)(s+t)= | | -4s+12=-8-4s | | 5-2x=37-6x | | 36a^2-49= | | 3x-5=-17 | | 8x-3=4x-15 | | e^3x-1=4 | | z=12x-y | | 7x+5=6x-2 | | 0.9x-0.3(3-x)=4.5 | | 2(2m-3)-3(2m-1)=9 | | 1-9x=82 | | 6z-3=-2-52 | | 8-2(10-4)=z | | 8-2(10-4)= | | 8x-8=8-8x+12 | | 4x+3=5x+11 | | 25x^2-11x-25=0 | | -7y+13+8y=-6 | | (3x^2-2y-2)-(4x^2+y)= | | (z+330+330)=330 | | 4x+20+3x+15=21 | | z(330+330)=330 | | (2y^2-y+2)-(-y^2+6y)= | | 5x+5-3x-6=0 | | -3-12=-4 | | (2x^2+7x+1)-(8x^2+x)= | | 8n-15=n-43 | | 2x+1-x+1=0 |